Carbon‐based perovskite solar cells: From single‐junction to modules. Issue 1 (4th October 2019) - He, Rui; Huang, Xiaozhou; Chee, Mason; Hao, Feng; Dong, Pei
Abstract: Perovskite solar cells (PSCs) have attracted more and more attention in the scientific community due to their high performance and simple fabrication process. In the past few years, emerging technologies have made manufacturing large‐scale PSC modules possible. However, stability and fabrication issues still limit the modularization and commercialization of PSCs. Carbon materials have been widely used in PSCs to overcome these challenges due to their excellent optical, electrical, and mechanical properties. In addition, the hydrophobic properties of certain carbon materials are highly effective at protecting the perovskite film from moisture and improving the stability of PSCs. All these superior properties have made carbon one of the most promising materials to fabricate future high‐performance PSC modules with long service lifetimes. In this review, recent developments of carbon‐based materials in different layers of single‐junction PSCs will first be discussed, with an emphasis on functionalities related to PSCs' stability and modularization. Then, current improvements and future discussions in the manufacturing of monolithic PSC modules will be reviewed in detail. Abstract : Due to carbon's unique properties, tremendous works on carbon‐based perovskite solar cells (PSCs) with high efficiency and stability have been reported. In this article, recent developments of carbon‐based single‐junction PSCs and PSC modules will be reviewed with an emphasis on functionalities related to PSCs' stability and modularization. In addition, current improvements and future developments in monolithic PSC modules manufacturing will also be discussed in detail.